Adapted compressed sensing for effective hardware implementations : a design flow for signal-level optimization of compressed sensing stages /: a design flow for signal-level optimization of compressed sensing stages. ([2018]) - Mangia, Mauro; Pareschi, Fabio; Cambareri, Valerio; Rovatti, Riccardo; Setti, Gianluca
No abstract available